Does Entrepreneurship create enough Jobs in Europe? A Note - Miltiades N. Georgiou (Max Planck Institute of Economics, 2006)
In the present note an effort will be made for a contribution to economic theory by extending the discussion paper Entrepreneurship, Regional Development and Job Creation: The Case of Portugal by R. Baptista, V. Escarta and P. Madruga, MPI, # 0605, in which the authors conclude (among others) that entrepreneurship creates jobs and reduces unemployment. This extension will be feasible by estimating the total economy's entrepreneurship reward for Western European countries and relating it with the total economy's unemployment rate. A regression based on the estimation of total economy's entrepreneurship reward will yield the same main results with the above article not only for Portugal but also for all Western European countries, that in any Western European country entrepreneurship creates enough jobs to reduce unemployment. This generalization with panel data econometric analysis is based on the discussion paper A Practical Method to Measure Entrepreneurship's Reward: A Note by M. N. Georgiou, MPI, #3805.
Keywords: M13; E24; 330; entrepreneurship; unemployment